A Disturbance Accommodating Estimator for Bilinear Systems - Saif, Mehrdad (American Control Conference, 1993, 1993)
In this article, an approach for designing a reduced order estimator for a class of nonlinear systems driven by external completely unknown and time varying disturbances is presented. The estimator's error dynamics in this case is completely independent of the input. Necessary and sufficient conditions for existence of the estimator along with numerical examples are presented.